Social prescribing in cardiology: rediscovering the nature within us. (2nd August 2019) - Howarth, Michelle; Lister, Craig
Abstract : Personalised care is integral to the delivery of the NHS England Long Term Plan. Enabling choice and supporting patients to make decisions predicated on 'what matters to them', rather than 'what is the matter with them' is a fundamental part of the NHS vision. Social prescribing uses non-medical, asset-based, salutogenic approaches to promote this personalised paradigm, and places the patient central to decision making. This article discusses how personalised care can be used to help people with cardiovascular disease using socially prescribed 'nature-based' interventions to support the pre-habilitation and rehabilitation of patients with cardiovascular disease. The concept of personalised care outlined and the significance of salutogenic principles as a complementary approach to the pathogenic model is discussed. The authors argue that this seemingly novel approach to using nature-based interventions can help promote wellbeing for people with cardiovascular disease as part of the wider personalised agenda.